Effect of menstrual phase on the surgical treatment of ovarian cysts. (3rd October 2017) - Song, Taejong; Kim, Mi Kyoung; Kim, Mi-La; Jung, Yong Wook; Yun, Bo Seong; Seong, Seok Ju
Abstract: This study aimed to determine whether the menstrual cycle affects operative bleeding and postoperative ovarian reserve in patients undergoing laparoscopic ovarian cystectomy. A total of 155 patients who had undergone laparoscopic ovarian cystectomy were classified into the follicular phase ( n = 84) and luteal phase ( n = 71) of the menstrual cycle. The primary outcome measures were operative blood loss and the rate of decline in ovarian reserve, as calculated by measuring serial serum anti-Müllerian hormone (AMH) levels preoperatively and 3 months postoperatively. No significant difference in the baseline demographics, operative blood loss ( p = .984), the rate of decline in ovarian reserve ( p = .945), and other surgical outcomes were observed between both the groups. These results demonstrate that the menstrual cycle had no influence on the operative blood loss and ovarian reserve during laparoscopic ovarian cystectomy. Therefore, the menstrual cycle is not an important factor to determine the optimal timing of ovarian cystectomy. Impact statement: What is already known on this subject?: The menstrual cycle results in periodic changes in haemostasis and blood flow in the reproductive organs. What do the results of this study add?: These results demonstrate that the menstrual cycle had no influence on the operative blood loss and ovarian reserve during laparoscopic ovarian cystectomy. What are the implications of these findings for clinical practice and/or further research?: The menstrual cycle is not an important factor to determine the optimal timing of ovarian cystectomy.